Francis Bacon e a nova indução: reforma do entendimento e restauração do homem - Motta, Carlos Jacinto Nascimento (2015)
The PhD. thesis here offered has as its aim the presentation of the Baconian conception of induction, understood as an essential element for the realization of Francis Bacon s project of a Restauration of by means of a reform of learning and sciences. In his most important and influente work, the Instauratio Magna, Bacon highlights the need for a wide survey of both the knowledge and sciences already established in order to know which of these should be abandoned, which perfected and which still are in need of implementation. Once this is achieved, and with due governamental support, a new scientifical era was supposed to begin and many advancements would also be achieved by Humankind. Notwithstanding, as Bacon points out, the reformation of sciences demands a change in the proceedings used by the investigator, which, in turn, results in a reformulation of both the idea of experience and the pattern of inference. It also indicates that the new scientifical era demands the establishment of investigative communities instead of isolated researchers, so that common mistakes to human nature should be avoided. This change, however, could only be realized in a mind duly cleansed of prejudices caused by both the philosophical tradition and by the natural characteristics of Humankind. The first were supposed to be corrected by means of the purging of idols, i.e. false notions which inhabit our mind and are imposed by culture; the latter, being these the greatest impediments on account of having to do with human nature itself, would be corrected by means of three different modalities of help, which combined form the novum organum (the new induction) or the new pattern of Bacon s scientific inference. This new induction must be understood in the contexto of the need for reformulations which promote the necessary aid to the investigator, being the histories the aids to the senses, the tables of presentation of instances the aids to memory and the new induction (Novum Organum) the aid to reason. Thus, we understand that the best interpretative key as regards the Baconian epistemology is the proposal of a reform of human understanding, and not merely the reformation of the logic used in investigations. Such reform would possibilitate the emergence of a new man, gifted with new logical tools and which would cooperate with other researchers towards the aim of assembling a type of inferential device, a collective investigative machine